2018
DOI: 10.1002/aenm.201703008
|View full text |Cite
|
Sign up to set email alerts
|

Progress in Aqueous Rechargeable Sodium‐Ion Batteries

Abstract: LIBs), flow batteries like Ni-MH, Ni-Cd and Pb-acid, Na/NiCl 2 , Na-S, Li-O 2 , and Li-S batteries have been considered as potential energy storage devices for ESSs. [5][6][7] The flow batteries like Ni-MH, Ni-Cd, and Pb-acid were feasible in past, whereas the environment pollution and safe risk caused by these batteries have deviated away from the parameters of ESSs. Although the Li-O 2 and Li-S batteries appear to offer the great hope for ESSs by virtue of extremely high energy density, the extensive materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
233
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 345 publications
(236 citation statements)
references
References 124 publications
(189 reference statements)
1
233
0
2
Order By: Relevance
“…In the case of the electrode materials for ASIBs, the choice of electrode materials is limited due to the larger radius of Na + (0.102 nm) . Especially the anode materials, only few materials (activated carbon (AC), NaTi 2 (PO 4 ) 3 , polyaniline, and PPy) have been developed in recent years .…”
Section: Aqueous Rechargeable Batteries Using Monovalent Ions (Li+ Nmentioning
confidence: 99%
“…In the case of the electrode materials for ASIBs, the choice of electrode materials is limited due to the larger radius of Na + (0.102 nm) . Especially the anode materials, only few materials (activated carbon (AC), NaTi 2 (PO 4 ) 3 , polyaniline, and PPy) have been developed in recent years .…”
Section: Aqueous Rechargeable Batteries Using Monovalent Ions (Li+ Nmentioning
confidence: 99%
“…The use of an aqueous solution instead of organic liquids as an electrolyte solvent for DCBs would be safer and more environmentally benign. However, the narrow electrochemical stability window of aqueous electrolytes (<1.5 V) restricts their application in DCBs ,. Fortunately, the aqueous electrolytes with expanded electrochemical windows have been well established through increasing the salt concentration; and a state‐of‐the‐art aqueous electrolyte can withstand a voltage of 5.1 V vs. Li/Li + .…”
Section: Highly Concentrated Electrolytesmentioning
confidence: 99%
“…However, the narrow electrochemical stability window of aqueous electrolytes (< 1.5 V) restricts their application in DCBs. [124,[148][149][150] Fortunately, the aqueous electrolytes with expanded electrochemical windows have been well established through increasing the salt concentration; and a state-of-the-art aqueous electrolyte can withstand a voltage of 5.1 V vs. Li/ Li + . [151][152][153] Recently, Kondo et al reported a highly concentrated aqueous solution, 21 M NaFSI/H 2 O (salt-to-solvent MR = 1 : 3), in which the graphite cathode can be charged to 1.7 V vs. Ag/ AgCl (corresponding to 4.6 V vs. Na/Na + ) and showed a discharge capacity of 20 mAh g À 1 at 10 mA g À 1 .…”
Section: Aqueous-based Highly Concentrated Electrolytesmentioning
confidence: 99%
“…Among those batteries, particular attention has been paid for aqueous sodium-ion batteries (SIBs) due to the wide availability of sodium resources and reversible intercalation chemistry of Nastorage materials. [15][16][17][18][19] Differing from non-aqueous SIBs, they are additionally challenged by narrow electrochemical stability window of aqueous electrolytes and chemical corrosion of aqueous solutions on Na-storage electrode materials. In fact, most of reported Na-storage materials in the field of nonaqueous SIBs are ill-suited for aqueous SIBs.…”
Section: Introductionmentioning
confidence: 99%